PENGAWASAN DALAM PERSPEKTIF AL-QUR’AN DAN HADITS - Mardiah, Ainul (Kasta: Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2023)
Monitoring the process or ar-riqobah in every form of leadership is something that must exist and must be implemented. The accentuation of this activity is to research and check whether the implementation of planning tasks is really being carried out or not. This is also to find out whether there are deviations, abuses, and deficiencies in its implementation. If there is, then it needs to be revised. The function of supervision or control is one of the activities to make improvements, not activities to find faults. To be able to carry out supervision properly, the planning concept must exist and be clear. Without planning it is difficult to detect deviations and without knowledge of deviations, the control function will be very blurry. This paper aims to examine the concept of control, the term Controlling in the Qur'an and hadith, the function and purpose of Controlling, Controlling requirements, implementation of controlling in Islamic educational institutions.